Optimum design of outriggers in a tall building by alternating nonlinear programming - Kim, Han-Soo (Engineering structures, 2017)
•Optimum design of location and stiffness of multiple outriggers in a tall building is performed.•A new method for mixed-integer nonlinear programming (MINLP) is proposed and verified.•Piecewise quadratic interpolation is used to obtain a differentiable and semi-continuous function.•Finite element analysis (FEA) rather than analytic equations is utilized in the optimum design of outriggers. Optimum design of locations and areas of multiple outriggers in a tall building was performed by a newly developed method. The method proposed in this study alternates between integer nonlinear programming and real number nonlinear programming to solve mixed integer nonlinear programming. Piecewise quadratic interpolation is used to obtain a differentiable and semi-continuous constraint function using the discrete analysis results from finite element analysis. Three analysis models representing various tall buildings with outriggers were used to perform the optimum design of the outrigger, which is subject to the lateral displacement constraint. The results demonstrate that as the number of outriggers used was increased, the total volume of the outriggers decreased. However, the performance of the outriggers remained almost the same when the number of the outriggers was greater than two. The optimum locations of the outriggers were slightly higher than those from the analytical solutions with simplified assumptions. The proposed method can be effectively used in other structural engineering applications that involve FEA.